Save And Loan Credit Information System Based On Web - Eddis Syahputra Pane (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Pancuran Hidup Credit Union is a cooperative engaged in a savings and loan business that provides loans for its members. In its development often encountered an error due to lack of accuracy of employees in processing data processing transactions and savings and loans that still use the manual system that is using Microsoft office (Microsoft word and Microsoft Excel). This manual system is less effective because the savings and loan transactions that occur are higher so that the calculation is even more numerous, and therefore requires an information system. The purpose of this research is to create a web-based savings and loan information system that helps make it easier for employees to manage member data and savings and loan transactions at the Pancuran Hidup Credit Union. In this study the authors used the Waterfall Model analysis method. The SDLC waterfall model is often also called the linear sequential model or classic life path. Based on the problems that have been discussed and resolved through this report, the conclusion can be drawn about the Savings and Loan Information System for the Union of Living Credit Pekanbaru based on Web, namely: Information Systems can facilitate the cooperative in making reports more quickly and produce accurate data